EFEKTIFITAS KOORDINASI PENYELENGGARAAN PEMERINTAHAN DI KECAMATAN MALALAYANG KOTA MANADO - RAMPENGAN, BRIAN; LENGKONG, FLORENCE DAICY; DENGO, SALMIN (Sam Ratulangi University, 2018)
The purpose of this research is to know how the effectiveness of coordination in governance in KecamatanMalalayang Manado City.This research uses quantitative approach method. Informant of this research as many as 8 people that isMalalayang Sub-district Head, 4 people Leadership / Elements UPTD Department, and 2 Head of VerticalInstitution in work area Kecamatan Malalayang, and 1 Lurah. Data was collected using interview guidelines, whilethe analysis technique used was interactive model analysis from Miles and Huberman.Based on the results of data analysis, it is concluded that the coordination of government administration inKecamatan Malalayang viewed from the dimension of communication, the dimension of cooperation, thedimension of synchronization, and the dimension of integration / unity of action has not been optimally realizedeffectively but it is good enough.Based on the results of the research can be recommended: (1) Communication between work units in thekecamatan can be improved by the implementation of coordination meetings and other meetings regularly orperiodically, and the delivery of clear and timely information about the program / activity plan and itsimplementation to all work units which exists. (2) Cooperation among work units can be enhanced by creatingcooperation forums. (3) The synchronization of programs / activities can be enhanced by conducting joint planningactivities. (4) Integration / unity of action can be enhanced by arranging together the program / activity plan andits implementation.Keywords: Coordination, Implementation of District Government.